Prediction of objective and subjective career success by career anchors among lawyers and jurists - fatemeh samiee (مجله علوم روانشناختی, 2022)
Background: Various research has been done about job success in different strata of society. But, there is little research that has examined the career success of lawyers and jurists. Aims: The study aimed to predict career success (subjective and objective) through career anchors among lawyers and jurists in Isfahan in the year 2019. Methods: A descriptive-correlational design was utilized to study. Thus, 152 lawyers (65 females and 87 male) were selected through convenience sampling and answered to the study instruments that consisted of Career Success Questionnaire (Samiee et al., 2014) and Career Anchors Questionnaire (Schien, 1985). The data were analyzed using Pearson's correlation and multiple regression analysis. Results: The results of descriptive statistics showed that the highest career anchor was technical and functional competencies, and then, service and lifestyle related to work-family balance among lawyers and Jurists. Besides, the prevalence of subjective career success was more than objective career success. Also, technical and functional competencies, independence and service predicted of subjective career success (p<0.05). Moreover, technical and functional competencies and challenge predicted objective career success (p<0.05), which explained 20 and 15 per cent of the variances of subjective career success and objective career success. Conclusion: Based on the results of this study it can be concluded that the subjective and objective career success could be increased by increasing competencies, independence and challenging cases among lawyers and jurists.